A comparative analysis of psychological trauma experienced by children and young adults in two scenarios: evacuation after a natural disaster vs forced migration to escape armed conflict. (May 2018) - Myles, P.; Swenshon, S.; Haase, K.; Szeles, T.; Jung, C.; Jacobi, F.; Rath, B.
Abstract: Objectives: Little is known about the psychological trauma experienced by children and young adults (CYAs) following displacement after natural disasters vs migration from conflict zones. In both instances, the decision to leave is usually cast by the family, and the life of CYAs is suddenly disrupted by external circumstances. Study design: An anonymous survey. Methods: The same survey instrument, provided by the National Child Traumatic Stress Network (NCTSN), was used to survey self-reported health needs among CYAs during the aftermath of Hurricane Katrina (Health Survey for Children and Adolescents After Katrina) in October 2005–February 2006 and again during the peak of refugee arrivals in Berlin between October 2015 and March 2016. A weighted index to measure cumulative exposure to traumatic stresses during migration was developed along with an unweighted psychological impact score based on the 22-item NCTS psychological impact questionnaire. Spearman's correlation coefficient (rho) was used to assess the correlation between age and the two psychological impact indices. The two-tailed t -test was used to investigate differences in trauma experienced and psychological impact by gender. Logistic regression was used to investigate differences in types of traumatic stress experienced and psychological impact among CYAs displaced because of Hurricane Katrina and those seeking asylum in Berlin. Results: The Katrina cohort included a total of 1133 CYAs, the Berlin cohort, a total of 405 CYAs. The median age in the Katrina cohort was 6.73 years (standard deviation [SD] 5.67, range 0–24; 50.13% males) compared with 17.64 years (SD, range 0–24; 83% males) in the Berlin cohort. Comparative analyses were adjusted to age and gender and revealed significant differences between the two cohorts, both with regards to the amount of trauma experienced and the psychological impact. A statistically significant and moderate positive correlation was observed between trauma experienced and psychological impact of migration in the refugee population (rho = 0.4955, P  < 0.001); the correlation was less pronounced but still significant in the Katrina cohort (rho = 0.0942, P  = 0.0015). Free-text responses revealed that in addition to common concerns about health, housing and safety, refugees were also pre-occupied with language acquisition and the adaptation to a new culture. Conclusions: The observed differences in the experience and the consequences of trauma in displaced CYAs warrant additional investigation. It was replicated that human-made disaster seems to show more traumatising potential than natural disaster. Stakeholders need to be aware of the potential medium and long-term consequences of migration/evacuation and allocate resources accordingly. Highlights: Children and young adults in either cohort had seen their home or neighbourhood badly damaged. Hurricane victims had left their home in a rush and repeatedly during their lifetime. Refugees were more likely to have been hurt or witnessed others being injured or killed. Refugees were also significantly more likely to have been separated from family.